Preservation Of Art Culture As A Form Of Enhancing The Identity Of The Cireundeu Community As A Sunda Indigenous Ethnic Group - Michellina Agatha; Aldian Ramadhan; Annida Thian; Anissa Lestari Kadiyono (Universitas Negeri Medan, 2022)
Sundanese culture is a national heritage that must be preserved as an ethnic group feature in Indonesia. However, as time goes on, a growing number of young people are losing their knowledge of the history, culture, and traditions that constitute the foundation of Indonesian identity. The target of this research is the Sundanese people in Cimahi City, West Java. This research intends to raise the awareness of the people in the Cireundeu Community about the preservation of Sundanese art which has the potential to become a richness of tranditions as identity, characteristics, revenue sources and economic productivity, and others. The undertaking consisted of observing the Angklung Buncis and Karinding art activities. In its implementation, this study obtained data from the community and also art figures from West Java. The research was carried out by employing a qualitative method with triangulation techniques. The primary data was obtained from experts in the field of art, while secondary data was acquired from literature reviews. The findings of this study aim to conserve Sundanese arts, particularly angklung buncis and karinding, which have a significant and valuable impacts on the society. The people of Cireundeu can demonstrate that the preservation of traditional arts in the face of modernization has its own beauty and provides economic prosperity, as well as fosters a greater sense of cultural pride in society.